2020
DOI: 10.3201/eid2612.201266
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oral Rabies Vaccines in the Elimination of Dog-Mediated Human Rabies Deaths

Abstract: S ince the advent of Pasteur's germ theory and the general acceptance that infectious diseases do not develop spontaneously, humankind has strived to reduce and eliminate pathogens that pose a serious public health threat. Incorporating routine vaccinations to control human diseases such as pneumonia, diarrhea, pertussis, measles, and polio contributed to the prevention of >10 million human deaths during 2010-2015 (1). Intensive global efforts toward disease eradication have focused on only a few diseases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…This study demonstrates that a high percentage of both bait acceptance and vaccination coverage can be achieved in free-roaming dogs using the oral bait handout and retrieve method. As the free-roaming dog population plays a key role in the transmission of rabies among dogs [ 4 ], it is essential to target these animals during vaccination campaigns. Most free-roaming dogs cannot be easily handled and restrained for parenteral vaccination, limiting the ability of MDV-campaigns to achieve vaccination coverages required to eliminate the rabies virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrates that a high percentage of both bait acceptance and vaccination coverage can be achieved in free-roaming dogs using the oral bait handout and retrieve method. As the free-roaming dog population plays a key role in the transmission of rabies among dogs [ 4 ], it is essential to target these animals during vaccination campaigns. Most free-roaming dogs cannot be easily handled and restrained for parenteral vaccination, limiting the ability of MDV-campaigns to achieve vaccination coverages required to eliminate the rabies virus.…”
Section: Discussionmentioning
confidence: 99%
“…Oral vaccination of wildlife has been successfully used to control rabies in different wildlife species around the world and it has also been suggested for dogs that are inaccessible for parenteral vaccination [ 4 ]. We studied the feasibility and field effectiveness of the use of oral rabies vaccine targeting free-roaming dogs as a complementary tool to control rabies in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study assessing the immune response of the 3rd-generation oral rabies vaccine strain SPBN GASGAS in local, free-roaming dogs under Southern African conditions. In settings where traditional parenteral methods have failed to reach adequate vaccination coverages against rabies, oral rabies vaccines can be very helpful in reaching adequate herd immunity (15), particularly in free-roaming dogs, which are considered to play a key role in the transmission of rabies (16,22,23). In great parts of Africa, actually, most free-roaming dogs are owned and are deemed accessible for parenteral vaccination at MDV campaigns (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…To increase vaccination coverage in these hard-to-reach dogs, the concept of oral rabies vaccination (ORV) of dogs as a complementary tool to mass parenteral dog vaccination has been proposed (14). Unfortunately, it is still the most underused of all tools in the fight against dog-mediated rabies (15), however, the concept has gained reviving interest in recent years (16)(17)(18)(19)(20). In fact, by targeting free-roaming and partly inaccessible dogs, ORV does not only increase the vaccination coverage of the overall dog population (16,21) but also reaches those animals that are considered to play a key role in the transmission of rabies (16,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Oral rabies vaccination has been shown to be a powerful tool to control and ultimately eliminate rabies from targeted reservoir species in different settings around the world [ 32 , 33 , 34 , 35 ]. It is suggested that ORV can contribute significantly to the elimination of dog-mediated rabies in areas with a high number of animals inaccessible for parenteral vaccination [ 36 ]. One of the pre-requisites for ORV is a suitable bait.…”
Section: Discussionmentioning
confidence: 99%